Extracellular haemoglobin upregulates and binds to tissue factor on macrophages: Implications for coagulation and oxidative stress - Bahl, Neha; Winarsih, Imelda; Tucker-Kellogg, Lisa; Ding, Jeak Ling (Thrombosis and Haemostasis, 2014)
The mechanisms of crosstalk between haemolysis, coagulation and innate immunity are evolutionarily conserved from the invertebrate haemocyanin to the vertebrate haemoglobin (Hb). In vertebrates, extracellular Hb resulting from haemolytic infections binds bacterial lipopolysaccharide (LPS) to unleash the antimicrobial redox activity of Hb. Because bacterial invasion also upregulates tissue factor (TF), the vertebrate coagulation initiator, we asked whether there may be functional interplay between the redox activity of Hb and the procoagulant activity of TF. Using real-time PCR, TF-specific ELISA, flow cytometry and TF activity assay, we found that Hb upregulated the expression of functional TF in macrophages. ELISA, flow cytometry and immunofluorescence microscopy showed binding between Hb and TF, in isolation and in situ. Bioinformatic analysis of Hb and TF protein sequences showed co-evolution across species, suggesting that Hbβ binds TF. Empirically, TF suppressed the LPS-induced activation of Hb redox activity. Furthermore, Hb desensitised TF to the effects of antioxidants like glutathione or serum. This bi-directional regulation between Hb and TF constitutes a novel link between coagulation and innate immunity. In addition, induction of TF by Hb is a potentially central mechanism for haemolysis to trigger coagulation.
Keywords: Haemolysis; lipopolysaccharide; sepsis; oxidative stress; co-evolution of haemoglobin and tissue factor